The Rule of Rules : Morality, Rules, and the Dilemmas of Law - Alexander, Larry, 1943- (Duke University Press, 2001)
Analysis of jurisprudential debates about the nature of law through a general investigation of the reasons for and optimal structures of authoritative rules and the moral and practical dilemmas created by those rules.